Prevalence of blindness and outcomes of cataract surgery in Hainan Province in South China - Li, Emmy Y; Liu, Yingpeng; Zhan, Xingkai; Liang, Yuan Bo; Zhang, Xiujuan; Zheng, Chongren; Jhanji, Vishal; Xu, Ping; Chang, David F; Lam, Dennis S C (Ophthalmology (Rochester, Minn.), 2013)
To define the prevalence of blindness and visual impairment (VI) in people in rural Hainan using the rapid assessment of avoidable blindness (RAAB) and to report the outcomes of cataract surgery among the residents. Population-based, cross-sectional survey. A total of 6482 rural residents of the Hainan province. A total of 136 clusters, each of which consisted of 50 people aged ≥50 years, were selected through probability-proportionate-to-size sampling. Door-to-door visits were performed by 2 outreach teams. Visual acuity (VA) was measured on site, and those with VA <6/18 in either eye were examined by an ophthalmologist. Causes of blindness and VI were determined. The causes of poor visual outcome after cataract surgery were evaluated. Information regarding barriers to receiving surgery was collected by trained interviewers. Prevalence and causes of blindness (VA <3/60), severe VI (SVI) (VA <6/60 but ≥3/60), and VI (VA <6/18 but ≥6/60) based on presenting VA (PVA) were assessed. Outcomes of cataract surgery performed in public and private hospitals and charitable organizations were compared. A total of 6482 subjects were examined (response rate, 95.3%). The sample prevalence of blindness was 4.4% (95% confidence interval [CI], 2.0-6.8). The prevalence of SVI and VI was 1.9% (95% CI, 0-4.3) and 9.9% (95% CI, 7.6-12.2), respectively. Age and sex were associated with increased prevalence of blindness, SVI, and VI. Overall, cataract accounted for approximately 60% of blindness and SVI. Of the 524 eyes that had received cataract surgery, 87.2% had intraocular lenses implanted, 21% had a poor visual outcome (PVA <6 /60), and 20% had a borderline visual outcome (PVA <6/18 but ≥6/60). Eyes that received surgery in charitable organizations had a higher rate of intraocular lens implantation and good visual outcome (VA ≥6/18) compared with eyes that were operated on elsewhere. The prevalence of blindness, SVI, and VI was high among rural residents in Hainan. Cataract remained the leading cause of avoidable blindness. Outcomes of cataract surgery performed in public hospitals were suboptimal. Quality-control initiatives should be introduced to improve cataract surgery outcomes.